The Use Of EU Structural Funds By Enterprises In The Lodz Region; Wykorzystanie funduszy strukturalnych UE przez przedsiebiorstwa w regionie łod́zkim - Tomasz Dorozẏnśki; Janusz Sẃierkocki; Wojciech Urbaniak (Comparative Economic Research. Central and Eastern Europe, 2013)
The issue of how to stimulate economic growth and development remains an open question. The EU structural funds are meant to help solve the problem at the regional level within the framework of the cohesion policy. Only some of these funds are used to directly subsidize businesses that are the engines of growth in a market economy. This paper aims to evaluate whether structural funds have played a positive and significant role in the development of enterprises in a region which does not belong to the economic leaders in Poland. It is based on the results of a direct study, statistical data and evaluation reports, as well as on the economic literature. The direct study was conducted in 2011. It focused on micro-economic projects supported by EU funds in the Lodz region. Interviews were conducted with representatives of 80 enterprises, which had completed at least one such a project. We conclude that the subsidies from structural funds have positively stimulated the modernization of the companies, albeit on a limited scale. – – Celem artykułu jest wyjasńienie sposobu wykorzystania funduszy strukturalnych UE przez przedsiebiorstwa z wojewod́ztwa łod́zkiego i ocena ich wpływu na gospodarke regionu, ktoŕy nie nalezẏ do gospodarczej czołoẃki w Europie i w Polsce. Podstawe do wyciagania wnioskoẃ stanowia wyniki badania bezposŕedniego przeprowadzonego w 2011 r. wsŕod́ przedstawicieli 80 firm, ktoŕe ukonćzyły co najmniej jeden projekt unijny w regionie łod́zkim. Głoẃna uwage posẃiecono projektom inwestycyjnym, wspoĺfinansowanym z Europejskiego Funduszu Rozwoju Regionalnego w ramach Regionalnego Programu Operacyjnego Wojewod́ztwa Łod́zkiego. W artykule wykorzystano roẃniezḋane statystyczne, literature przedmiotu oraz wyniki badanéwaluacyjnych. Z przeprowadzonych analiz wynika, zė dla wielu badanych przedsiebiorstw fundusze unijne stanowiły wazṅe zŕod́ło finansowania inwestycji i walki o rynkowe sukcesy. Tym niemniej, ze wzgledu na bardzo ograniczona liczbe i mała wartosćṕrojektoẃ nie da sie nimi ułatwicŕozwoju przedsiebiorstw i regionu w szerszej skali.
Keywords: 330; EU funds; Lodz Region; enterprises